IDENTITAS LINTAS BUDAYA: PUISI HAIKU JEPANG BERBAHASA BALI - I Nyoman Darma Putra; Ida Bagus Jelantik Sutanegara Pidada; Ida Ayu Laksmita Sari (LP2M ISBI Bandung, 2023)
The development of Indonesian and regional literature in the Archipelago is not only determined by internal conditions but also by external influences. Several years ago in Bali, an anthology of haiku in Balinese was published, which was clearly influenced by the form of haiku, traditional Japanese poetry. This article analyzes Balinese haiku collected in two anthologies, namely Bikul (Mouse, 2014) and Bubu (Fishtrapped, 2015), both by I Ketut Aryawan Kenceng. By applying a qualitative approach, this research data was collected through literature studies and interviews with poets and observers of modern literature in the Balinese language. The data were analyzed using structuralism and semiotic approaches. The results of the study show that Balinese haiku provides a cross-cultural identity (Japanese and Balinese) for modern Balinese literature. The results of this study contribute to our efforts to understand that this hybrid poem strengthens the opinion of scholars who say that Bali is an open fortress, meaning that it remains open to accepting outside influences but firmly maintains its artistic and cultural identity.Keywords: modern Balinese literature, Balinese language, haiku, cross-cultural identity, Japan